Beasts made of night - Onyebuchi, Tochi (Beasts made of night, 2017)
After he eats the sin of a royal, Taj, a talented aki, or sin-eater who consumes the guilt of others whose transgressions are exorcised from them by powerful but corrupt Mages, is drawn into a plot to destroy the city, and he must fight to save the princess he loves and his own life.